Synthesis, Characterization, and Antimicrobial Activity of Some New Thiophene Derivatives and Crystal Structure of Ethyl [4-(2-Thienylmethylene)Aminophenoxy]Acetate - Al-Taifi, Elham A.; Al-Aghbari, Sama A. Z.; El-Ossaily, Yasser A.; Yeap, Guan-Yeow; Marae, Islam S.; Ibrahim, Omaima F.; Bakhite, Etify A. (Springer Nature, 2022)
This work describes facile routes towards the synthesis of some novel thiophene derivatives. Thus, condensation of thiophene-2-carboxaldehyde with 4-aminophenol furnished the Schiff base, 2-[(4-hydroxyphenyl)iminomethyl]thiophene. Reaction of the Schiff base with ethyl chloroacetate or chloroacetamide gave ethyl (4-(2-thienylmethylene)aminophenoxy]acetate and [4-(2-thienylmethylene)aminophenoxy]acetamide respectively. Alkylation of the Schiff base with some 1-bromoalkanes afforded alkyloxyphenylaminomethylenethiophene derivatives. The title compounds were characterized by elemental analysis, infrared (IR) and 1H NMR spectroscopy. In addition, the molecular structure of ethyl [4-(thiophene-2-ylmethylene)aminophenoxy]acetate was further confirmed by single-crystal X-ray diffraction which its crystals are found to be monoclinic and the space group is P21/c with the lattice parameters a = 8.961(2) ?, b = 12.236(3) ?, c = 12.996(3) ?, ? = 93.629 (3) and V = 1422.1(5) ?3. Moreover, all synthesized compounds were screened in vitro for their antimicrobial activity and promising results obtained.